PENGARUH POLA ASUH ORANG TUA TERHADAP KECERDASAN EMOSIONAL PESERTA DIDIK DI SMP NEGERI 1 MANUJU - Suciati; Bunyamin, Andi; Syahrul, Muhammad; Syahid, Akhmad; Sampurno, Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of parenting styles on the emotional intelligence of students at SMP Negeri 1 Manuju, Gowa Regency. The study employs a quantitative approach with a correlational research design. The population consists of 93 students from SMP Negeri 1 Manuju, Gowa Regency. Data collection was conducted using a Likert-scale questionnaire administered to respondents to gather information regarding parenting styles and student emotional intelligence. The obtained data were analyzed using the Statistical Product and Service Solutions (SPSS) program, utilizing descriptive analysis, validity testing, reliability testing, assumption testing, simple linear regression analysis, t-testing, and the coefficient of determination. The results indicate that parenting styles have a positive and significant influence on students' emotional intelligence. This is evidenced by the simple linear regression equation Y = 17.062 + 0.428X. The partial test results show a calculated t-value of 5.942—exceeding the t-table value of 1.661—with a significance value of 0.000 (< 0.05); consequently, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. The correlation coefficient (R) of 0.559 indicates a positive relationship of moderate strength between parenting styles and emotional intelligence. Meanwhile, the R-square value of 0.272 indicates that parenting styles contribute 27.2% to students' emotional intelligence, while the remaining 72.8% is influenced by other factors not examined in this study. Thus, parenting style is one of the factors playing a role in the development of students' emotional intelligence.